"Les charmants contours de la danseuse". A portrait of humour in Traité du Style by Louis Aragon - Perrot, Mathieu (Romanica Olomucensia, 2019)
Louis Aragon's work has rarely been read for his humoristic views. Nevertheless, humour was a serious enough concept for the poet to write a few pages about it in his 1928 poetic essay Traité du style, where he connects humour to poetry. And yet, how is to portray such a protean abstraction as humour if not by poetically listing what it is not? In addition to providing a close reading of a passage in Traité du style, this paper discusses examples of humour taken from Aragon's novels and poetry, as well as critical thoughts from Breton, Bergson, and Freud about humour. It also draws on recent studies by Jean-Marc Moura and Dominique Noguez. In Aragon's poetics, humour is nothing but a performance, a movement that any definition stops and destroys. It must remain indefinite to keep its subversive potential, its intrinsic and subtle evocations which make it "the negative condition of poetry", i.e. its counterpart. For Aragon, humour is an awareness, an anti-bourgeois attitude that questions dogma and habits and that rejects any frame or definition because of their limited answer-like status. Through wit and freedom, humour and its ambiguities mock and play with systems and ideologies, undermining authority.
Keywords: poetry; Louis Aragon; humour; portrait; revolt; anti-bourgeois